Eficácia de um programa de educação em saude e sentidos e significados atribuídos ao Diabetes Mellitus e aos cuidados com os pés por pacientes em risco - Ligia de Loiola Cisneros (2005)
Diabetes Mellitus is an important public health problem in all countries of the world. Among all the complications faced by diabetics, one of the most frequent and disable is the diabetic foot syndrome, the precursor to lower- extremity amputation in these patients. The prevention of this outcome is an aim world wide. To achieve this target, foot care program, can be a therapeutic possibility. This study was designed a) to evaluate the preventive efficacy of an educational program to diabetics at risk of foot ulceration and lower-extremity amputation and b) to investigate the sense and meaning of the diabetes disease to the patients and their families and how an educational program influences prevention of the diabetic foot syndrome complications.Investigations were carried out in a total of 53 patients with diabetes mellitus, identified at risk of foot lesions. Both quantitative and qualitative study were conducted. A randomized controlled trial was designed in order to measure the efficacy of an educational program. The clinical-qualitative method provides the understanding of the senses and the meanings attributed to diabetes and foot care by the patients and their families. There were no significant differences in the occurrence of foot ulceration between the groups: in the intervention group the rate of incidence of ulcers was 38.1% compared with 51.1% in the control group. Although, 83.3% of the patients who presented an ulcer relapse were allocated in the control group versus 16.7% from the intervention group, the difference was not significant (p = 0.119). The life table analysis showed that, one year of study in the intervention group, patients had a probability of 75% to have no one occurrence of ulcer compared with 61% of the control group. It was noticed a tendency in the control group to survive a shorter time without an ulcer but the test to compared curves of expectancy of surviving had not showed a statistically significant difference (p = 0.362). Listening to the patients experiences revealed that each one of them plunged into the Illness in a particular way, by each one´s knowledges and desires, trying to survive on a complex management, lifelong and damageable disease. Their testimonies showed an universe of hidden interactions behind the patients through their dialogs with their caretakers about the necessary work to be adopted to cope with the disease.The differences between the groups in preventing ulcers occurrence and relapses were not statistically significant. However, this evaluation should be interpreted with caution. The clinical trial can not be the best method to measure the efficacy of an educational program for patients. The prevention of foot complications for diabetics is a complex and multi factor process, as the disease and its management. The responses to restraints caused by the diabetes are socially formed, pointing us to a world of actions, beliefs and values. The cognitive, socials and affectives filters of the patients must be considered in preparing the health care program as they determine the way the individuals will receive and interpret these informations. The diagnosis of Diabetes Mellitus implies in a rearrangement of the patient´s life and their families. Many diabetics need help to take care of their feet. Therefore, the therapeutic education must be also oriented to family members/caretakers . We came from a reduced vision of the patient to a more complex dimension. From care of his/her foot to a person´s plenitude, fighting to survive despite all the adversities of life.